MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN TEKNIK THE POWER OF TWO DI SDN 019 PANDAU JAYA KECAMATAN SIAK HULU - Desnianti, Desnianti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the result of the study of grade 6 students of SD Negeri 019 Pandau Jaya Kecamatan SiakHulu which is still low. This study aims to improve student learning outcomes by using the power of two techniques.From the data analysis performed seen improvement of student learning outcomes from cycle I up to cycle II. Incycle I, from 30 students 21 students have succeeded in learning or mastery 70,00% classical. While 9 students or30.00% has not reached the Minimum Exhaustiveness Criteria set at number 70. The average grade is 62.33 orMedium. That is, learning has not succeeded, and the author continues to cycle II. Viewed from the result oflearning cycle II, from 30 students 28 or 93.33% and 2 students or 06.67% unfinished. The average grade is 80.33or the category is very good. The highest score is 100 and the one lowest is 40. This proves that the improvement oflearning using The power of two technique on the students of class VI SD Negeri 019 Pandau Jaya Kecamatan SiakHulu can improve student learning outcomes.